Macahydantoins A and B, two new thiohydantoin derivatives from Maca (Lepidium meyenii): Structural elucidation and concise synthesis of macahydantoin A. Issue 17 (26th April 2017) - Yu, Mu-Yuan; Qin, Xu-Jie; Shao, Li-Dong; Peng, Xing-Rong; Li, Lei; Yang, Han; Qiu, Ming-Hua
Graphical abstract: Highlights: Macahydantoins A and B, two novel thiohydantoin derivatives, were isolated from Lepidium meyenii . Stereochemistries were determined by ECD calculation. The chemical synthesis of macahydantoin A was achieved. Abstract: Macahydantoins A (1 ) and B (2 ), two new thiohydantoin derivatives with an unprecedented skeleton, were isolated from maca ( Lepidium meyenii ). Their structures and absolute configurations were fully established by extensive spectroscopic and computational methods. The totally chemical synthesis of macahydantoin A was achieved via benzylamine and methyl piperidine-3-carboxylate hydrochloride through nucleophilic addition and intramolecular dehydration condensation.